Implementasi Pembiasaan Tadarus Al-Qur’an Untuk Menanamkan Nilai-Nilai Keagamaan pada Siswa di MTs Al-Imaroh Cikarang Barat - Nur Azizah Syarifah; Tajuddin Nur; Yayat Herdiyana (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The habit of tadarus al-qur'an plays an important role in learning activities because it is an activity in the form of worship which is believed to be able to get closer to Allah, can increase faith and piety which has implications for a positive attitude. . and behavior in students. The importance of habituation of tadarus al-Qur'an in instilling religious values in students is to create a generation of Muslims who are able to instill and practice according to religious teachings. This writing aims to find out the activities of tadarus al-qur'an habituation in instilling religious values in students at MTs Al-Imaroh. In this method, the author uses qualitative research methods, namely research that emphasizes the study of data analysis from literature studies using a descriptive research approach. The results of this study indicate that the habit of tadarus al-Qur'an has an impact on the religious values of students at MTs Al-Imaroh. With the habit of tadarus al-Qur'an students can instill basic religious values such as Faith, Islam, Taqwa Ikhlas, Tawakal, Gratitude and Patience in everyday life.